2012
DOI: 10.1074/mcp.m111.013524
|View full text |Cite
|
Sign up to set email alerts
|

Use of Proteinase K Nonspecific Digestion for Selective and Comprehensive Identification of Interpeptide Cross-links: Application to Prion Proteins

Abstract: Chemical cross-linking combined with mass spectrometry is a rapidly developing technique for structural proteomics. Cross-linked proteins are usually digested with trypsin to generate cross-linked peptides, which are then analyzed by mass spectrometry. The most informative cross-links, the interpeptide cross-links, are often large in size, because they consist of two peptides that are connected by a cross-linker. In addition, trypsin targets the same residues as amino-reactive cross-linkers, and cleavage will … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 58 publications
0
32
0
Order By: Relevance
“…20 Other researchers used different cross-linking reagents and PK digestion to study the structural differences between rPrP and rPrPβ. 21 These approaches used recombinant PrP or regions of PrP Sc that were not glycosylated. Mass spectrometry-based study of PrP Sc structure has mainly focused on the non-glycosylated N-terminal region of PrP Sc .…”
Section: Mass Spectrometry-based Study Of the Structure Of Prp Scmentioning
confidence: 99%
“…20 Other researchers used different cross-linking reagents and PK digestion to study the structural differences between rPrP and rPrPβ. 21 These approaches used recombinant PrP or regions of PrP Sc that were not glycosylated. Mass spectrometry-based study of PrP Sc structure has mainly focused on the non-glycosylated N-terminal region of PrP Sc .…”
Section: Mass Spectrometry-based Study Of the Structure Of Prp Scmentioning
confidence: 99%
“…Other studies have contributed in the elucidation of the structure of prion protein, by using proteinase K for protein digestion in the process of molecule identification (Petrotchenko et al, 2012).…”
Section: Scrapiementioning
confidence: 99%
“…Numerous factors have led to this dominance, but essentially reliance on trypsin means that peptide identifications depend on good sequence coverage of tryptic cleavage residues, Arg and Lys. Cross-linking via amine-reactive NHS-ester based cross-linkers (DSS/BS3/sulfo-SDA) targets Lys residues, which subsequently become non-cleavable by trypsin following cross-linking reaction, the prevalence of Lys and Arg residues becomes even more important (42). It has been shown that cross-linked residue pair identification can be boosted by the use of alternative proteases to trypsin, including proteinase K, Asp-N, Glu-C, Lys-C and Lys-N (18,42,43).…”
Section: Experiments Protocolmentioning
confidence: 99%
“…Cross-linking via amine-reactive NHS-ester based cross-linkers (DSS/BS3/sulfo-SDA) targets Lys residues, which subsequently become non-cleavable by trypsin following cross-linking reaction, the prevalence of Lys and Arg residues becomes even more important (42). It has been shown that cross-linked residue pair identification can be boosted by the use of alternative proteases to trypsin, including proteinase K, Asp-N, Glu-C, Lys-C and Lys-N (18,42,43). We decided to employ Glu-C to target acidic residues for cleavage for all targets alongside standard trypsin digestion.…”
Section: Experiments Protocolmentioning
confidence: 99%